Effects of preoperative oral carbohydrate solution intake on thermoregulation - Ozer, Ayse B.; Demirel, Ismail; Kavak, Burcin S.; Gurbuz, Oguz; Unlu, Serap; Bayar, Mustafa K.; Erhan, Omer L. (Int Scientific Literature, Inc, 2013)
Background: We aimed to investigate the oral carbohydrate solution administered preoperatively on thermoregulation. Material/Methods: The study included 40 female patients under general anesthesia. Patients were randomly divided into 2 groups: Group CONT (stopped oral implementation 8 h before the operation) and Group CHO (800ml oral carbohydrate fluid 8 h before the operation and 400ml oral carbohydrate fluid 2 h before the operation). Patients were monitored as standard and temperature probes were placed. Temperatures were recorded immediately before anesthetics induction, 5 min after the anesthetics induction, and in the post-anesthesia care unit (PACU) every 10 min. Mean skin temperature (Tsk), mean body temperature (Tb), and vasoconstriction threshold were estimated. Results: In general, we observed a decrease in tympanic temperature and Tb following anesthetic administration in groups, and increase in Tsk, and an increase in all 3 of these levels in the recovery unit. Tympanic temperature was significantly higher at 25, 55, 65, and 95 min after induction in Group CONT compared to Group CHO (p<0.05). Tsk was found to be lower in Group CONT compared to Group CHO in almost all periods. In PACU, it was found that the tympanic temperature was higher in Group CONT compared to Group CHO at 60 min (p<0.05). Postoperative shivering score was found to be significantly higher in Group C (p<0.01). Vasoconstriction threshold was higher in Group CONT than Group CHO. Conclusions: Oral carbohydrate solution administered was established to have effects thought to be negative on tympanic temperature, vasoconstriction, and vasoconstriction threshold.
Keywords: oral carbohydrate; thermoregulation; general anesthesia